Bureaucratic Reform by Building Trust in Citizens: Best Practices from Local Online Complaints - Dwiyanto Indiahono (Indonesian Association for Public Administration, 2021)
The purpose of this study is to provide an overview of the success of the Banyumas Complaint Outlet (Lapak Aduan Banyumas/ LAB) in increasing public trust in the government. One of the goals of bureaucratic reform is to build citizens’ trust, but it is rarely discussed how the bureaucracy initiates bureaucratic reform by building trust in citizens. This research used qualitative research methods, data collection techniques used are interviews, observation, and documentation. The data analysis techniques used were interactive data analysis and content analysis. LAB offers a framework that gives trust to the public to complain, many complaints from the public will create external pressure from the bureaucracy to make improvements to bureaucratic performance. Performance improvements of the bureaucracy will increase public trust. The increase in public trust in the government is evidenced by the high interest of citizens to provide suggestions and input to the government regarding public services or facilities. A simple complaint system and quick response has proven to strengthen public trust. Bureaucratic reform can be started by earning citizens’ trust.